Analysis of the factors influencing the process of attracting adults to regular physical activity at the local level - L.N. Shlepakov; O.N. Varenyk (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The purpose of the study - the optimization of system performance sport for all and the establishment of effective organizational relationships between the various entities at the municipal level. Conducted a survey of the ordinary citizens of working age (610 persons), 100 specialists, 2 expert groups (15 and 18 respectively). The factors influencing the process of attracting people to the motor activity: individual, social, economic, infrastructure. Classified factors comprehensively assessed the extent and consequences of the influence of each process on the system at the level of local communities. A set of actions to minimize the impact of constraints and maximizing the manifestations of factors conducive to attracting people to regular physical training and sports. The basic directions of activity: access of the general public to low cost sports facilities, tools, equipment, creation of environmentally safe and comfortable environment for practicing physical activity, overcoming the deficit of public awareness of the organization of motor activity.